PERANAN ORANGTUA DAN GURU BK DALAM MENGATASI DEGRADASI MORAL SISWA DI SEKOLAH MENENGAH ATAS NEGERI 1 KECAMATAN PAYAKUMBUH - Fina Diningsih Lestari; Afrinaldi; Muhiddinur Kamal; Fadhilla Yusri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is motivated by the occurrence of common violations that are often found in SMAN 1 Kec. Payakumbuh, the problem of moral decline that occurs in students such as skipping school, being undisciplined, students coming late to school, smoking, being alpha, leaving, jumping over fences, and dating has gone beyond reasonable limits, this also occurs in SMAN 1 Kec. Payakumbuh. The research method is qualitative, data collection in the study through Observation, interviews, and documentation, the subjects in this study were 1 guidance and counseling teacher, 5 students and 5 parents of students. The purpose of the study was to determine the role of parents in overcoming moral degradation of students at SMAN 1 Kec. Payakumbuh; to determine the role of BK teachers in overcoming moral degradation of students at SMAN 1 Kec. Payakumbuh. Research The results of this study indicate that the way guidance and counseling teachers provide direction/guidance in overcoming moral degradation of students has been running well as seen from the counseling process carried out for students, namely by providing information services, advice, motivation and concluding the results of the counseling process. The method used is smiling to greet students, greeting students as the initial stage in the counseling process, the next method is to provide appropriate responses to students' feelings, telling students to do something such as providing group guidance services, group counseling services, individual counseling. And conclude all the results of the discussion with students so that it is easier for guidance and counseling teachers to solve student problems.